Hubungan Peran Keluarga, Pola Makan, Dan Status Gizi Terhadap Pencegahan Diabetes Mellitus Gestasional Di BPM Wilayah Kerja Kecamatan Payung : (The Relationship between Family Roles, Diet, and Nutritional Status to the Prevention of Gestational Diabetes Mellitus in the BPM Work Area of Payung District - Anggraini, Silvia (Dohara POAJ, 2024)
Introduction: Prevention of Gestational Diabetes Mellitus is an effort that individuals deliberately make to avoid or control blood sugar levels so as not to interfere with pregnancy and the health of mothers and babies. This study aimed to determine the direct and indirect effects and the magnitude of the influence of information sources, family roles, diet, physical activity, and nutritional status on the prevention of Diabetes Mellitus in pregnant women in Payung Health Center in 2023. Methods: This research was taken from primary data using a questionnaire. The sample used was 60 respondents with a cross-sectional design. The research was conducted in December 2022-January 2023. The cross-sectional analysis method was used. Results: The results showed that there was a relationship between the role of kelaura (p-value 0,030); diet (p-value 0,.003); and nutritional status (p-value 0,053) on the behavior of preventing gestational diabetes mellitus in pregnant women. Discussion: This study concludes that there is a relationship between family roles, diet, and nutritional status on the behavior of preventing gestational diabetes mellitus in pregnant women in the working area of Payung District in 2023. Suggestions for mothers to always maintain their health during pregnancy to avoid complications during pregnancy.